Double-Brillouin Frequency Spacing Multi-Wavelength Brillouin Erbium Fiber Laser in Double Cavities Configuration - Lip Zhan Hong,; Tan Sin Jin,; Sulaiman Wadi Harun,; Cheng Xiau San, (Journal of Advanced Research in Applied Sciences and Engineering Technology, 2023)
Multi-wavelength fiber laser has great potential for use in dense wavelength-division multiplexing (DWDM) systems, sensors, and microwave photonics. This paper presents a multi-wavelength Brillouin erbium fiber laser (MW-BEFL) with double-frequency Brillouin spacing of approximately 0.176 nm between each adjacent Stokes. The proposed setup utilizes double cavities configuration for odd and even-order Brillouin Stokes to propagate separately in the system. This configuration is flexible as it can be transformed into a single-spacing MW-BEFL by swapping the ports of the circulator; it can also extract the odd-orders Brillouin Stokes by relocating the OSA in the cavity. Up to 25 double-spaced Brillouin Stokes are obtained with a tuning range of 30 nm. The first 8 Stokes have peak power variation within ± 3.7 dB and an average signal-to-noise ratio of 20 dB.